Analisis Putusan Hakim Mengenai Hubungan Seksual Incest (Studi Kasus Pengadilan Negeri Palopo) - Jeki Alang; Ahkam Jayadi (Alauddin Law Development Journal (ALDEV), 2022)
This study entitled "Judicial Review of Judges' Decisions Regarding Sexual Relationships in the Family Environment (Incest) (Case Study at the Palopo District Court", the problems are: 1). How to prove criminal acts against perpetrators of sexual relations in the family environment (Incest) in the Palopo District Court and 2). How is the Judge's decision in establishing evidence of a criminal act against the perpetrator of sexual relations within the family (Incest) at thethe Palopo District Court?